Positron emission tomography molecular imaging to monitor anti-tumor systemic response for immune checkpoint inhibitor therapy. - Xing, Xiaoqing; Zhao, Qing; Zhou, Jinyun; Zhou, Rui; Liu, Yu; Qin, Xiyi; Zhang, Mingrong; Zhong, Yan; Wang, Jing; Tian, Mei; Zhang, Hong (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Immune checkpoint inhibitors (ICIs) achieve a milestone in cancer treatment. Despite the great success of ICI, ICI therapy still faces a big challenge due to heterogeneity of tumor, and therapeutic response is complicated by possible immune-related adverse events (irAEs). Therefore, it is critical to assess the systemic immune response elicited by ICI therapy to guide subsequent treatment regimens. Positron emission tomography (PET) molecular imaging is an optimal approach in cancer diagnosis, treatment effect evaluation, follow-up, and prognosis prediction. PET imaging can monitor metabolic changes of immunocytes and specifically identify immuno-biomarkers to reflect systemic immune responses. Here, we briefly review the application of PET molecular imaging to date of systemic immune responses following ICI therapy and the associated rationale.